The Iconography of the Mythological Characters of Dante’s “Divine Comedy” in the Manuscripts of the 14th–15th Centuries: Possible Role and Origins - Miroshnik, Alina D.; Pozhidaeva , Anna V. (Actual Problems of Theory and History of Art, 2023)
The history of illustration of the “Divine Comedy” by Dante in the 14th–15th centuries rarely attracts the attention of researchers. Nevertheless, a careful analysis of the manuscripts would make it possible to understand how the text was illustrated, full of means of artistic expression and citations from ancient sources, many of which were largely unknown to the authors of the iconographic program. This study is devoted to the visualization of selected mythological characters based on six manuscripts, four of which are fully illustrated (Egerton MS. 943, first half of the 15th century (c. 1320–1350), British Library, London; MS. M 676, 1345–1355, Morgan Library, New York; Yates Thompson MS. 36, 1444 – c. 1450, British Library, London; Urb. Lat. 365, c. 1480, Vatican Library, Vatican); and two partially (Cod. Ital. 1, c. 1333–1350, University Library, Budapest; Chantilly 0597, c. 1330–1340, Condé Museum, Chantilly).
Keywords: Divine Comedy by Dante; iconography of mythological characters; illustrated manuscripts